Creating A Bilingual Website of Food Delights Souvenir for Anugerah Oleh-Oleh Khas Malang - Nicholas Krisna Widjanarko; Bambang Suryanto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Anugerah Oleh-Oleh Khas Malang is one of the souvenir shops located at Jl. Trunojoyo No. 81, Malang, East Java. This shop offers a variety of Malang specialty products such as tempeh chips, fruit chips, and apple-based products. In addition, the shop is strategically located and provides friendly service to customers. However, the store still faces challenges in terms of promotion, especially promotional media that reach domestic and international customers effectively. Therefore, the researcher designed and developed a bilingual website as a promotional tool in Indonesian and English, introducing the store's history, contact information, operating hours, location, prices, and product descriptions, complete with photos and videos of the store. This study applied the Design and Development Research (DDR) model from Richey and Klein, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation (ADDIE). Data collection was conducted through interviews with staff, field observations, and questionnaires. The bilingual website was designed using CMS WordPress to make it easier to create an attractive and user-friendly website. The bilingual website then validated by two experts in the fields of language and IT to ensure the quality of the content and technical aspects. Subsequently, a field test was conducted on 66 respondents from various nationalities to assess the clarity of information, ease of use, and visual appearance of the website. The testing results showed very positive feedback, with an average satisfaction score of 4.5 out of 5. These results indicate that the bilingual website effectively functions as an educational and promotional tool. Additionally, the website bridges language barriers and supports the preservation of local culture, making it suitable for use by tourists and professional industry.